Human respiratory syncytial virus diversity and epidemiology among patients hospitalized with severe respiratory illness in South Africa, 2012–2015 - Ziyaad Valley-Omar; Stefano Tempia; Orienka Hellferscee; Sibongile Walaza; Ebrahim Variava6; Halima Dawood; Kathleen Kahn; Meredith McMorrow; Marthi Pretorius; Senzo Mtshali; Ernest Mamorobela; Nicole Wolter; et al. (My University, 2015)
Background: We aimed to describe the prevalence of human respiratory syncytial virus (HRSV) and evaluate associations between HRSV subgroups and/or genotypes and epidemiologic characteristics and clinical outcomes in patients hospitalized with severe respiratory illness (SRI). Methods: Between January 2012 and December 2015, we enrolled patients of all ages admitted to two South African hospitals with SRI in prospective hospital-based syndromic surveillance. We collected respiratory specimens and clinical and epidemiological data. Unconditional random effect multivariable logistic regression was used to assess factors associated with HRSV infection. Results: HRSV was detected in 11.2% (772/6908) of enrolled patients of which 47.0% (363/772) were under the age of 6 months. There were no differences in clinical outcomes of HRSV subgroup A-infected patients compared with HRSV subgroup B-infected patients but among patients aged <5 years, children with HRSV subgroup A were more likely be coinfected with Streptococcus pneumoniae (23/208 11.0% vs. 2/90, 2.0%; adjusted odds ratio 5.7). No significant associations of HRSV A genotypes NA1 and ON1 with specific clinical outcomes were observed. Conclusions: While HRSV subgroup and genotype dominance shifted between seasons, we showed similar genotype diversity as noted worldwide. We found no association between clinical outcomes and HRSV subgroups or genotypes.
Keywords: human respiratory syncytial virus, severe respiratory illness, South Africa